Fish Community Structure in The Coastal Mangrove Ecosystem of Cemara Kulon Village Indramayu Regency, Indonesia - Titin Herawati; Muhamad Pauwwaz; Zahidah Zahidah; Izza Mahdiana Apriliani; Ayi Yustiati (Jurnal Biodjati, 2024)
The mangrove ecosystem of Cemara Kulon Village has the potential for fishery resources which has decreased in line with various anthropogenic activities. This study aims to determine the composition of fish and analyze the status of the fish community structure and its relation to the physical-chemical aspects of the waters in the mangrove ecosystem of Cemara Kulon Village. This research was conducted over a period of three months  in the mangrove ecosystem of Cemara Kulon Village. The method used in this research was  descriptive quantitative purposive and composite sampling at 3 research stations. Parameters observed in this study were relative abundance, diversity, uniformity, dominance, and the relationship between community structure and aquatic physico-chemical parameters. During the study, 508 fish were caught, consisting of 20 species from 16 families. The value of diversity was in the moderate category with a ranged of 1.87-2.50; the uniformity value was in the moderate category with a ranged of 0.41-0.46 and the dominance value was in the low category with a ranged of 0.11-0.22.   Based on the results of the Canonical Correspondence Analysis (CCA) revealed that fish diversity was affected by light transparency and DO, the uniformity of fish was  affected by temperature, and the dominance of fish was affected by ammonia. The fish community structure was categorized as unstable which was influenced by water quality.